2017
DOI: 10.1002/2017ja024232
|View full text |Cite
|
Sign up to set email alerts
|

Geospace system responses to the St. Patrick's Day storms in 2013 and 2015

Abstract: This special collection includes 31 research papers investigating geospace system responses to the geomagnetic storms during the St. Patrick's Days of 17 March 2013 and 2015. It covers observation, data assimilation, and modeling aspects of the storm time phenomena and their associated physical processes. The ionosphere and thermosphere as well as their coupling to the magnetosphere are clearly the main subject areas addressed. This collection provides a comprehensive picture of the geospace response to these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 33 publications
1
57
0
Order By: Relevance
“…This indicated that the latitude dependence and altitude dependence of temperature changes during geomagnetic storms are not well characterized and understood, especially for the altitude below 100 km and in latitude regions outside the auroral oval. During the 2013 St. Patrick's Day (17 March) geomagnetic storm (Verkhoglyadova et al, 2016;Zhang et al, 2017), the temperature measured by the SABER instrument onboard the TIMED satellite and the Solar Occultation For Ice Experiment (SOFIE) instrument onboard the Aeronomy for Ice in the Mesosphere (AIM) satellite provides a good opportunity to study the latitude and altitude dependence of temperature changes during geomagnetic storms, which will be the main subject of this paper.…”
Section: 1029/2018gl078039mentioning
confidence: 99%
See 2 more Smart Citations
“…This indicated that the latitude dependence and altitude dependence of temperature changes during geomagnetic storms are not well characterized and understood, especially for the altitude below 100 km and in latitude regions outside the auroral oval. During the 2013 St. Patrick's Day (17 March) geomagnetic storm (Verkhoglyadova et al, 2016;Zhang et al, 2017), the temperature measured by the SABER instrument onboard the TIMED satellite and the Solar Occultation For Ice Experiment (SOFIE) instrument onboard the Aeronomy for Ice in the Mesosphere (AIM) satellite provides a good opportunity to study the latitude and altitude dependence of temperature changes during geomagnetic storms, which will be the main subject of this paper.…”
Section: 1029/2018gl078039mentioning
confidence: 99%
“…By analyzing the temperature data derived from a meteor radar at Andenes (69°N), Pancheva et al (2007) found a significant cooling (~25 K) at~90 km during storms in late October 2003. Subsequently, Nesse Tyssøy et al (2010) (Verkhoglyadova et al, 2016;Zhang et al, 2017), the temperature measured by the SABER instrument onboard the TIMED satellite and the Solar Occultation For Ice Experiment (SOFIE) instrument onboard the Aeronomy for Ice in the Mesosphere (AIM) satellite provides a good opportunity to study the latitude and altitude dependence of temperature changes during geomagnetic storms, which will be the main subject of this paper. Nesse Tyssøy et al (2008) noted that the temperature variation below 90 km was dominated by atmospheric waves and was not related to the SPEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first storm called the St. Patrick's Day geomagnetic storm of 17 March 2015 was the most severe (min Dst = −223 nT) storm of current solar cycle 24. The interplanetary origin of this St. Patrick's Day storm and its consequences on the Earth's F and E regions of ionosphere and magnetosphere is one of the most studied space weather events of solar cycle 24 with most articles published under JGR‐Space Physics special collection on “Geospace system responses to the St. Patrick's Day storms in 2013 and 2015” (Zhang et al, ). Astafyeva et al () presented a global ionospheric response of this storm using multi‐instrument (GPS receiver, Ionosonde, and Satellite) observations.…”
Section: Introductionmentioning
confidence: 99%
“…The St. Patrick Day geomagnetic storm of 17–19 March 2015 was the most intense storm of the current solar cycle 24 with a minimum Dst index of −222 nT. This storm is the most studied space weather event of solar cycle 24 with most articles published under JGR‐Space Physics special collection on “Geospace system responses to the St. Patrick's Day storms in 2013 and 2015” (Zhang et al, ). Using multi‐instrument (GPS receiver, Ionosonde, and Satellite) data, Astafyeva et al () analyzed the global ionospheric response of the March 2015 storm and found a complex effect varying with longitude and hemisphere, showing both positive and negative ionospheric storms in the TEC.…”
Section: Introductionmentioning
confidence: 99%